Ocorrência de depressão em população geriátrica de uma equipe de saúde da família de Fortaleza-Ce - Bezerra Neto, Antônio George (2014)
This thesis aims to analyze, through the application of the Geriatric Depression Scale (GDS-15), the prevalence of depression in a population of elderly assisted by the staff of the Family Health Fortaleza - CE. Cross-sectional study with 78 elderly residents in area ascribed a team of Family Health Fortaleza. The data collected for analysis were obtained by means of 1) interviews using a structured questionnaire containing socio - demographic and clinical , 2) cognitive assessment (Mini Mental State Examination - MMSE) and 3) application of the Geriatric Depression Scale (GDS-15) , from January to April 2014. Results indicated that 62.8 % of the population are women, with a prevalence in the age group between 60-69 years (61.5 %), with 1-4 years study and family income 1-2 minimum wages. The majority of the sample consists of retired (79.5 %), living with partner and family and, in part, have hypertension. The prevalence of depression was 21,3%. The results showed that no significant association between depression and socio - demographic and clinical variables. There was an inverse correlation between cognitive deficit and depression, only in the females (r= -0,518; p<0,001) from 60 to 69 years (r= -0,566; p=0,001) and between old what work (r= -0,482; p=0,033). The diagnosis of geriatric depression was similar to other studies, justifying early interventions aimed at this population.